Prenatal practices, health outcomes and pregnancy intention among mothers in the municipality of Rizal, Occidental Mindoro - Paredes, Ana Carmela Mari F. (Animo Repository, 2016)
Through the Millennium Development Goals, countries, including the Philippines, have committed to reduce maternal mortality by three quarters and child mortality by two thirds from 1990 to 2015. Over the years the government has managed to decrease the number of neonatal deaths; however, little improvement has been made in maternal mortality. The aim of this study is to describe the prenatal care practices and pregnancy intention of selected mothers in the municipality of Rizal, Occidental Mindoro. Furthermore, the study determined the association of prenatal care practices to knowledge on pregnancy risks and complications, access to maternal health care providers and social support; and health outcomes. A total of 60 women who have delivered for the past 3 years and currently residing in the area, were interviewed using a semi structured interview schedule. Various statistical methods were used to describe the relationship of the variables used. Results show that majority of the respondents have an inadequate level of knowledge regarding pregnancy risks and complication, a high level of social support for their pregnancy, and a high level of access to maternal health care providers. Moreover, the results suggest that respondents have a high level of prenatal care practices, both traditional/personal and modern, and have no intention to have another pregnancy. Three statistically significant associations were found: between level of knowledge and modern prenatal care practices; between frequency of visit to doctors and modern prenatal care practices; and between the uses of traditional/ personal prenatal care practices and having maternal and newborn complications. Findings have implications for the ways maternal and infant health services may be further provided in the rural communities surveyed.